A Casual Relationship Between Fluctuations in Foreign Exchange Rates and Foreign Direct Investment - Tharshiga, P.; Rathiranee, Y. (Wayamba University, 2024)
The study aims to analyze the causal relationship between fluctua- tions in foreign exchange rates and foreign direct investment. For this purpose, data from January 2015 to November 2023 was analyzed using EViews soft- ware. An ADF unit root test was conducted to determine if the data contained a unit root. Lag order selection was used to identify an optimal number of lags, and the VAR Granger causality test was employed to investigate the causal re- lationship between variables. The results indicate unidirectional causality from FDI to Euro, JPY to GBP, and FDI to GBP at twelve lags. Additionally, bidirec- tional causality is observed from JPY to FDI and USD to FDI at the 5% signifi- cance level when twelve lags are applied. In March 2016, FDI experienced a decrease due to a global financial crisis, but this did not impact the country's exchange rate. Similarly, the outbreak of COVID-19 in March 2020 did not sig- nificantly affect the exchange rate. However, the political crisis in Sri Lanka in March 2022 had an adverse effect on the exchange rate, showing a negative pat- tern during this period. The fluctuations in exchange rates and changes in foreign direct investment are greatly influenced by government policies and practices. It is therefore crucial for policymakers to make well-informed decisions to sustain stable FDI and exchange rates, particularly during financial crises, to maximize benefits.
Keywords: Foreign exchange rate fluctuations,; Foreign direct investment; JPY; GBP; Euro; USD